Social choice and equilibrium - Morkeliūnas, A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. И. Моркелюнас. Групповой выбор и равновесиеA. Morkeliūnas. Grupinis parinkimas ir pusiausvyra